ESTIMATING GEOELECTRIC FOR THE CLEAN WATER NECESSITY PREDICTION (CASE STUDY: ABDUL RACHMAN SALEH AIRPORT MALANG) - Hirijanto, Hirijanto; Yuwono, Endro; Maaruf, Annur (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2022)
Abdul Rachman Saleh Airport of Malang plays a significant role for the air transportation in Malang and its surrounding. The services provided in Malang Abdul Rachman Saleh airport are expected to be the alternative solution to the high number of prospective passangers in Juanda Airport. However, it gives an impact in the sense of the high public interest of utilizing Abdul Rachman Saleh Airport in Malang. Increasing airport service activities requires the fulfillment of supporting facilities and infrastructure, including raw water supply. Upon critical condition such as a sudden damage, it only relies on the PDAM Malang regency water suppy and in the long run, it is prone to face water shortages. Therefore, it is required to have a pure water supply with raw water need analysis, raw water necessity estimation, and also the exploration for potential water resources that can be used as clean water supply provider at Abdul Rachman Saleh airport. The geoelectric method was used to explore the potential groundwater supply through a layer feature beneath the surface and the possibility of groundwater and minerals at a certain depth. Investigations related to topographic, physiographic, geomorphological, geological and hydrogeological conditions were carried out to analyze the potential for underground water around the Abdul Rachman Saleh airport area. Several location points were surveyed and measured to determine estimates of the availability of groundwater that were detected. The results of the analysis show that there is potential for groundwater availability at three locations around the airport area which can be used as raw water reserves to meet the needs of clean water supply which is predicted to reach 0.9 liters / second in 2036. As a raw water reserve, the need for clean water for Abdul Rachman Saleh airport Malang services is predicted to be fulfilled.